Anatase‐Rutile TiO2@V4C3Tx MXene for Omnidirectional Electrocatalytic Water Splitting - Neermunda Shabana; Punnoli Muhsin; Ya‐Yun Yang; Pi‐Tai Chou (Advanced Materials Interfaces)
Abstract The quest for composite materials with unique features that each component, inherently, does not have is always an aspirational but challenging task. Among Transition metal oxides (TMOs), TiO2 emerged as a prototype due to its earth abundance, environmental friendliness, and cost‐effectiveness, which has shown high activity for photocatalytic hydrogen evolution. Unfortunately, TiO2 is inert for electrocatalytic hydrogen evolution reaction (HER) because it has poor electrical conductivity and unfavorable hydrogen adsorption/desorption behavior. Herein the revitalization of inert TiO2 for overall water splitting, i.e., both HER and oxygen evolution reaction (OER) is reported by anchoring rutile‐anatase (a/r) TiO2 nanoparticles on the ‐OH/‐F terminated V4C3Tx MXene, giving an a/r TiO2@V4C3Tx heterostructure. The synergetic effect showcases remarkable pH‐independent HER activity with an overpotential of 35, 39, and 82 mV in 0.5 m H2SO4, 1 m KOH, and 1 m phosphate‐buffered saline (PBS) respectively. The catalyst also exhibits a pH‐independent OER activity with the lowest overpotential of 217, 267, and 292 mV in 1 m KOH, 0.5 m H2SO4, and 1 m PBS respectively, that outperforms pure TiO2. These findings, for the first time, support the success of anatase‐rutile TiO2@V4C3Tx MXene in omnidirectional performance, with low overpotential and pH independence, which pave an avenue for finding cost‐effective catalysts in overall water splitting.